Analisis Actio Pauliana Sebagai Bentuk Perlindungan Hukum Bagi Kreditor Kepailitan : Studi Putusan Nomor 06/Pdt.Sus.Gugatan Lain-Lain AP/2020/PN.Niaga.Jkt.Pst. Jo. Nomor 27/Pdt-Sus PKPU/2015/PN.Niaga.Jkt.Pst. - Aji Suryanata; Yudho Taruno Muryanto (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research aims to determine whether actio pauliana is an appropriate legal remedy in providing legal protection for creditors in bankruptcy cases. It also aims to determine the basis of the judge's considerations in Verdict No. 06/Pdt.Sus.Gugatan Lain-lain-AP/2020/PN.Niaga.Jkt.Pst. Jo. No. 27/Pdt-Sus-PKPU/2015/PN.Niaga.Jkt.Pst. This research is a normative legal research with statutory and case approach. The type of data used is secondary data. The technique used in collecting legal materials in this research is literature study. This research uses syllogism analysis technique and deductive thinking pattern, using major premises and minor premises which then these premises can produce conclusions. Based on this research, it is found that actio pauliana is an appropriate legal remedy in providing legal protection for creditors who are harmed by debtors in bankruptcy cases because there is internal legal protection and external legal protection in accordance with Isnaeni's legal protection theory used as an analysis. The basis of the judge's consideration used as the curator's right to file an actio pauliana lawsuit is Article 47 paragraph (1) and Explanation of Article 3 paragraph (1) of the Bankruptcy Law, then in deciding the case used as the analysis material, the judge uses Article 41 and Article 42 of the Bankruptcy Law.